Relationship analysis of FaPYR1 and FaCHS genes encoding fruit ripening of three species of strawberries (Fragaria spp.) fruit (Biodiversitas Journal of Biological Diversity, 2023)
Abstract.  Aristya GR, Dyatama GR, Zuyyina C, Maulina NTA, Arif MF, Musthofa A, Kasiamdari RS. 2023. Relationship analysis of FaPYR1 and FaCHS genes encoding fruit ripening of three species of strawberries (Fragaria spp.) fruit. Biodiversitas 24: 87-97. The difference in the phenotypes characters and gene expressionof strawberries (Fragaria spp.) is influenced by changes in hormone signaling mechanisms to receptors due to the adaptation to various types of environments. Abscisic acid (ABA) is one of the phytohormones that plays a role in the growth and development of strawberries, response to environmental stress, and fruit ripening. One of the ABA receptors is the PYR1 protein which is encoded by FaPYR1 gene. ABA also plays a role in inducing the FaCHS gene associated with pigmentation in strawberry fruit. This study aimed to analyze the relationship between FaPYR1 and FaCHS gene sequences in three strawberry species encoding fruit ripening. The FaPYR1 (585-633  bp) and FaCHS (90-93  bp) genes from three strawberries species namely Fragaria moschata, Fragaria vesca L. 'Californica', and Fragariax ananassa 'Festival' were successfully amplified. The results of the gene family relationship analysis of FaPYR1 gene sequences showed a close relationship with the comparative three species to GenBank, with a genetic distance value of 0.01-0.02. Meanwhile, FaCHS gene sequences from three species of strawberries showed a close relationship with the comparable FaCHS gene sequence from GenBank, with a genetic distance of 0.1-0.2.